Biodegradation of oily wastes and sludges - Lee, L. B. (1997)
Improper disposal of petroleum hydrocarbons can cause hazardous effects to both the environment and life. Used and unused oils from several sources contribute to the problems of oil contamination in the environment. Physico-chemical treatment methods are not completely effective as the emission of secondary wastes such as wastes gases and sludges are in the concern. Biodegradation which utilizing microorganisms is therefore an environmentally sound alternative. A case study on microbial isolation and screening of various oily contaminated samples showed that Pseudomonas sp. and Vibrio sp. were present in all oil samples. It was found that the degradation rates depend on incubation temperature.